2021
DOI: 10.5603/ep.a2021.0034
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone serum concentration kinetic profile in critically ill patients undergoing continuous renal replacement therapies: a prospective observational study

Abstract: Introduction: Elevated serum parathormone (PTH) levels have been observed in acute kidney injury and are related to calcium-phosphate metabolism disturbance, decreased renal production of 1,25 dihydroxyvitamin D3, impaired renal PTH excretion, and other renalindependent factors. There are no data regarding PTH concentration kinetics in critically ill patients undergoing continuous renal replacement therapies (CRRT) in an intensive care setting. The primary objective of this study was to investigate trends in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Czarnik et al compared PTH in critically ill cases with renal failure undergoing continuous renal replacement therapies, with or without sepsis. They found higher PTH levels in septic patients [ 46 ]. The increased parathyroid response in sepsis may be due to increased catecholamines during sepsis that could act on β-adrenergic receptors on the parathyroid gland, stimulating PTH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Czarnik et al compared PTH in critically ill cases with renal failure undergoing continuous renal replacement therapies, with or without sepsis. They found higher PTH levels in septic patients [ 46 ]. The increased parathyroid response in sepsis may be due to increased catecholamines during sepsis that could act on β-adrenergic receptors on the parathyroid gland, stimulating PTH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind, randomized control trial by Zaloga and Teres, PTH was found to be elevated in critically ill patients in the absence of kidney disease, suggesting that PTH may be a stress hormone [ 11 ]. Similarly, Czarnik et al observed elevated PTH levels among hemodialysis patients during an acute illness with sepsis and a reversal in a stable state [ 12 ].…”
Section: Discussionmentioning
confidence: 99%